Podcast Media Credibility as a Means of Fulfilling Public Information - A Renisyifa; S Sunarti; A Pebriyanti (Universitas Komputer Indonesia, 2022)
In this era of high speed of information flow, a lot of information has the potential to become fake news. Mass media is an essential means of fulfilling public information, so that public trust is greatly influenced by the credibility of the related information media. Podcasts are a new phenomenon in the digital era which has become one of the users of new media to find various information used by the public. This study aims to see how far the credibility of podcast media in conveying information to the public. The type of this research is descriptive qualitative research with phenomenological method. The subject of the research was carried out by observing several podcast platforms, the researcher was only limited to observing to check interview data with content publications on a number of these platforms. The results of this study indicate that the credibility of podcast media in fulfilling public information is quite high because it is one part of the clarification of circulating information by presenting themselves not as anonymous and carried out through in-depth research. Listening to a podcast about a particular theme can stimulate the audience's brain to receive information which is equivalent to reading a book. Information on a podcast is based on the podcaster's specialty. so that with the credibility built, podcasters are able to become accurate and reliable presenters and help stimulate the audience's mind to be able to think further and also imagine a visualization, think more critically, be creative, and get various interesting inspirations